(untitled) (Quinto Sol, 2017)
A great deal of ideological debates and political positions of the 20th century were associated to the use of the concept of totalitarianism. This usage, often abuse, developed an instrumental significance which was entangled in a petty comparative game between its different interpretations, along with a perception that diminished, or highlighted, nuances depending upon the interests or social status of who was using it. As stated by Enzo Traverso, only few terms ingrained in political culture are as ambiguous, pliable and polymorphous as the word totalitarianism. The word totalitarianism is part of the lexicon of all political trends and ideologies, nevertheless, throughout this article we will approximate to one particular usage; the one performed by a sector of argentine contemporary right-wings. More specifically, catholic right-wing with corporate tendency and, within it, the perspective created (in articles written from 1918, foregathered as books during the early 1940’s) by monsignor Gustavo Franceschi, an acknowledged social catholic intellectual.